Persian Manuscripts in Croatian Collections - Paić-Vukić, Tatjana (2012)
The presentation of the Persian manuscripts which are kept at the Croatian state institution: The Croatian Academy of Sciences and Arts, The National and University Library and The Croatian State Archives